Vozes e imagens da memória em Poemas, Novos poemas e Poemas escolhidos - Santos, Virgínia da Silva (2015)
The present dissertation has as objective to present a discussion of the relationship between literature and memory inside the following Jorge de Lima’s books: Poemas (1927), Novos Poemas (1929) and Poemas Escolhidos (1923). We choose the poems in which the memory is present. The memory could be present when it is related to the childhood, or when is related to the collective area. Our theoretical framework is compound of authors as Paul Ricoeur (2012), Maurice Halbwachs (2006), Henri Bergson (2010), Gaston Bachelard (1978), Agostinho (2011), Aleida Assmann (2011), and others writers who allow us to understand how memory works, and as well, the memory’s manifestations like keepsake, reminiscence and oblivion. The authors Fábio de Souza Andrade (1993), José Paulo Paes (1997), Ana Maria Paulino (1995), Leyla Perrone-Moisés (1990), Julia Kristeva (2012) are some of the literature scholars who also composed this dissertation’s theoretical framework.